Music of the Malaysian Philharmonic Orchestra (MPO) Forum 2 Finalists: Reflections on Malaysian Multiculturalism - Lena Pek Hung Lie, (Wacana Seni Journal of Arts Discourse, 2013)
The Malaysian Philharmonic Orchestra (MPO) Forum for Malaysian Composers 2 signifies the multicultural vibrancy of Malaysia. The finalists respectively promote cultural elements in their works. The appropriation of Eastern aesthetics, philosophy and cultural heritage into Western musical ideology are some of their compositional approaches. Moreover, various elements of Malaysian traditional art forms ranging from dance rhythms to ritual concepts and practices often emerge as an integral compositional component in their works. This article attempts to identify the compositional styles of Mohd Yazid Zakaria, Ng Chong Lim, Teh Tze Siew and Yii Kah Hoe by means of critical analysis on their selected works and interviews. This comprehensive investigation shows that their stylistic trends can be classified into two main categories, i.e., music influenced by Malay art forms, and music influenced by Chinese aesthetics. Mohd Yazid's works embody various aspects of Malay traditional art forms, whereas Teh and Ng's music demonstrate their affinity with Chinese philosophy and aesthetics. Straddling between these two categories is Yii's music that illustrates both Malay and Chinese elements with equal importance. In the light of their diverse musical styles in keeping with a multicultural concept, these four composers have much to contribute to the shaping of Malaysian art music of the 21st century. Malaysia as a multicultural society is clearly reflected in the works of these composers which this article further substantiates based on critical readings of the composers' works.